„Finnish Design“: Zur Genese eines Werbediskurses zwischen nationaler Selbstbehauptung und globalem Markt - Schalenberg, Marc (Österreichische Zeitschrift für Geschichtswissenschaften, 2010)
The article investigates into the origins of the Finnish Design discourse, which has proved so prominent and functional in recent years. While an infrastructure for the production and diffusion of arts-and-crafts items had been built up in Helsinki from the late 19th century onwards and Finland joined the vanguard of international modernism in the 1930s it took the difficult context of the Second World War and its immediate aftermath to firmly anchor the notion of specifically Finnish design. Items of everyday consumption, seemingly sharing certain characteristics, were thereby loaded with national connotations – an interpretation mirrored and amplified on international forums. Under the conditions of post-modern globalized markets this label has increasingly turned into a sales tool of an almost arbitrary, yet highly effective sort.